Hybrid absorbing boundary condition for piecewise smooth curved boundary in 2D acoustic finite difference modelling. Issue 4 (1st August 2018) - Li, Bei; Liu, Yang; Zhao, Yumin; Liu, Xin
Abstract : Flexible computational domains and their corresponding irregular absorbing boundary conditions (ABCs) have previously been shown to improve the efficiency of finite difference (FD) modelling. However, these proposed ABCs for irregular boundaries are based on irregular grid methods. Although they can improve geometric flexibility of FD modelling, irregular grid methods are still complex to implement due to computationally expensive meshing process. To avoid complex mesh generation, FDs in mesh-free discretisation have been developed for nontrivial geometric settings, where scattered nodes can be placed suitably with respect to irregular boundaries and arbitrarily shaped anomalies without coordinate mapping or mesh-element forming. Radial-basis-function-generated FD (RBF-FD) has been proven successful in modelling seismic wave propagation based on mesh-free discretisation. Using RBF-FD, we develop a hybrid ABC for piecewise smooth curved boundary in 2D acoustic wave modelling based on straightforward expanding strategies for sampled boundary and corner nodes. The whole irregular computational domain is combined by an objective zone and a transition zone separated by piecewise smooth curved boundary. Nodal distribution in the objective zone is adaptive to the model structure through special alignment and varying density of nodes, while the transition zone are designed for solving one way wave equation more easily and accurately in the presence of piecewise smooth curved boundary. Modelling examples for homogenous and heterogeneous models with differently shaped computational domains demonstrate the effectiveness of our proposed method. Abstract : Flexible computational domains with irregular absorbing boundaries can improve the efficiency of seismic modelling. We propose a hybrid absorbing boundary condition for piecewise smooth curved boundary in mesh-free discretisation based on radial-basis-function-generated finite difference modelling. Modelling examples in both homogeneous and heterogeneous media with flexibly shaped computational domain demonstrate the effectiveness of our proposed method.